ERROR ANALYSIS IN WRITING OF THE TENTH GRADE STUDENTS OF MAN 1 PALU - Intan, Nur; Jauhari Bandu, Darwis; Amelia, Yuni (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2020)
Error analysis is an activity to identify, classify and interpreted or describe the errors made by someone in speaking or in writing and it is carried out to obtain information on common difficulties faced by someone in speaking or in writing English sentences. For students, error analysis is needed to show them in what aspect in grammar which is difficult for them, to show the errors made by the students, to know the source or the cause of the error and how the students can learn from their mistakes in order that they will not make some errors repeatedly. The purpose of this research is to describe the type of grammatical error faced by students in writing. This research used descriptive qualitative method. This research was carried out in using descriptive writing text to find out what types of error made by students of the tenth grade students MAN 1 Palu in writing and what causes of the students error in writing. The result of the research showed that the tenth grade students MAN 1 Palu still made 41 errors in their writing. They are three classification of error based on surface strategy taxonomy. The high frequency of error is selection (63,41%), omission (26,82), and The lowest frequency of error is addition (9,75). On the other hand, the highest cause of error is carelessness (75,6%), %), first language (7 or 17,07 %), while the lowest cause of error is translation (7.31%).